An inter- laboratory proficiency testing exercise for rabies diagnosis in Latin America and the Caribbean. - Alfonso Clavijo; Mary H Freire de Carvalho; Lillian A Orciari; Andres Velasco-Villa; James A Ellison; Lauren Greenberg; Pamela A Yager; Douglas B Green; Marco A Vigilato; Ottorino Cosivi; Victor J Del Rio-Vilas (Public Library of Science (PLoS), 2017)
The direct fluorescent antibody test (DFA), is performed in all rabies reference laboratories across Latin America and the Caribbean (LAC). Despite DFA being a critical capacity in the control of rabies, there is not a standardized protocol in the region. We describe the results of the first inter-laboratory proficiency exercise of national rabies laboratories in LAC countries as part of the regional efforts towards dog-maintained rabies elimination in the American region. Twenty three laboratories affiliated to the Ministries of Health and Ministries of Agriculture participated in this exercise. In addition, the laboratories completed an online questionnaire to assess laboratory practices. Answers to the online questionnaire indicated large variability in the laboratories throughput, equipment used, protocols availability, quality control standards and biosafety requirements. Our results will inform actions to improve and harmonize laboratory rabies capacities across LAC in support for the regional efforts towards elimination of dog-maintained rabies.